Pos Gizi Remaja di SMA Negeri 12 Kota Jambi - Merita Merita; Tri Kusuma; Yolanda Wulan Sari; Rahmadiani Rahmadiani; Wisa Amelia Futri (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2020)
Abstract The centred approach of adolescents at school can prevent nutritional problems and improve daily nutrient intake. Therefore, the purpose of this service is the formation of adolescent nutrition posts. This activity was carried out in September 2019 until January 2020, in SMA Negeri 12 of Jambi City. The target is adolescents in the SMA Negeri 12 of Jambi City, who joined student council organizations. This activity consisted of (1) providing counseling with power point media, leaflets, posters, as well as pre-post test questions; (2) Practice monitoring of nutritional status and; (3) Formation of nutrition posts. The outputs of the community service activities are: (1) Effective and innovative leaflets and posters; (2) Application of balanced nutrition in adolescents and; (3) Establishment of adolescent nutrition posts. Based on the pre-test results it was known that the target had good knowledge about balanced nutrition and nutritional status of adolescents ie> 90% can correctly answer the questions on the post-test sheet. Therefore, it is expected that schools will be able to involve School Health Unit to provide information and health education specifically on the importance of balanced nutrition for adolescents.